Diagnosis of ischemic small bowel disease by measurement of serum intestinal fatty acid-binding protein in patients with acute abdomen : a multicenter, observer-blinded validation study - Kanda, Tatsuo; Tsukahara, Akihiro; Ueki, Kyo; Sakai, Yasuo; Tani, Tatsuo; Nishimura, Atsushi; Yamazaki, Toshiyuki; Tamiya, Yoichi; Tada, Tetsuya; Hirota, Masaki; Hasegawa, Jun; Funaoka, Hiroyuki; et al. (Journal of gastroenterology, 2011)
Background Intestinal fatty acid-binding protein (I-FABP) is a low-molecular-mass (15 kDa) cytosolic protein found exclusively in the epithelial cells of the small bowel mucosa. We aimed to evaluate the clinical usefulness of serum I-FABP measurement for the diagnosis of ischemic small bowel disease. Methods Patients with a clinical diagnosis of acute abdomen were recruited for this multicenter trial at one university hospital and nine city hospitals over a 13-month period. Serum I-FABP levels were measured in 361 eligible patients by an enzyme-linked immunosorbent assay using a specific monoclonal antibody. Results Of the 361 patients, 242 underwent surgery, and small bowel ischemia was diagnosed in 52 patients. The mean serum I-FABP level in the patients with small bowel ischemia was 40.7 ± 117.9 ng/ml, which was significantly higher than that in patients with non-ischemic small bowel disease (5.8 ± 15.6 ng/ml) and those with non-small bowel disease (1.8 ± 1.7 ng/ml). The serum I-FABP cutoff level for the diagnosis of small bowel ischemia was 3.1 ng/ml. Serum I-FABP was more efficient than conventional biochemical markers, in terms of sensitivity and positive and negative predictive values, in the diagnosis of small bowel ischemia. However, its specificity was slightly lower than that of creatinine phosphokinase or lactate dehydrogenase. The positive and negative likelihood ratios of serum I-FABP were 3.01 and 0.29, respectively. Conclusion Serum I-FABP measurement is a non-invasive method that is potentially useful for the efficient identification of patients with acute abdomen who are at risk of small bowel ischemia.